Neglected clubfoot in an adolescent treated with posteromedial release-Case Report. (Journal of Pakistan Orthopaedic Association, 2022)
Neglected clubfoot in adolescent is a challenge to treat for an Orthopedic surgeon. The aim of treatment is a pain free and cosmetically acceptable foot with near normal function. Different treatment modalities have been reported with variable results and include Ponseti method of casting, soft tissue release alone or with some bony procedure like triple arthrodesis, talectomy, and Ilizarov ring fixator. We present a case report of a neglected club foot in 18-year-old female treated with isolated posteromedial soft tissue release (PMR). We achieved a cosmetically acceptable pain free plantigrade foot.